Method for identifying microbial antigens that stimulate specific lymphocyte responses: application to Salmonella. - Warren, R L (1990)
Vaccine development and understanding of cellular immune stimulatory mechanisms have been impeded by the paucity of data on microbial antigens that stimulate protective immunity. We describe here a general method for identifying and isolating peptide antigens that specifically stimulate sensitized lymphocytes. First, Salmonella typhimurium C5 genomic DNA fragments were subcloned into Escherichia coli by use of the lambda gt11 expression vector. Next, antigens expressed by recombinant phage from this genomic library were tested for their capacity to stimulate proliferative responses in pooled lymphocytes obtained from BALB/c mice infected 14 days earlier with S. typhimurium. Of 2000 recombinant phages tested, 5 stimulated a polypeptide-antigen-specific proliferative response. Physical analyses of these 5 recombinant phages revealed cloned inserts of 0.5-2.4 kilobase pairs representing nonoverlapping regions of the C5 chromosome. Four of the five insert DNAs hybridized at high stringency to both S. typhimurium and Salmonella typhi total chromosomal DNA, suggesting that these pathogens of different host specificity share several antigenic determinants. Use of sensitized primary polyclonal lymphocytes provides a rapid and simple method for screening recombinant DNA libraries for clones that stimulate specific immune responses and avoids the use of cloned lymphocyte cell lines. This approach should be generally applicable to similar studies in different hosts of many other microbial pathogens.